Historical variations in the year-class strength of beaked redfish (Sebastes mentella) in the Barents Sea - Planque, B.; Johannesen, E.; Drevetnyak, K. V.; Nedreaas, K. H. (ICES Journal of Marine Science, 2012)
<qd> Planque, B., Johannesen, E., Drevetnyak, K. V., and Nedreaas, K. H. Historical variations in the year-class strength of beaked redfish ( Sebastes mentella ) in the Barents Sea. – ICES Journal of Marine Science, doi:10.1093/icesjms/fss014. </qd>The present work provides the first quantitative estimate of the historical fluctuations in the year-class strength of beaked redfish in the Barents Sea. The year-class strength index is based on scientific survey data collected by Norway and Russia during the past three decades. It is defined as the effective number of 0-group fish that will eventually enter the fishery. Uncertainties in the year-class strength indices are estimated using a statistical modelling approach, which accounts for observation errors. The reconstructed series indicate clear periods of high recruitment (late 1980s–early 1990s) and 8 years of near complete recruitment failure (1996–2003). The apparent recovery in recent years is highly uncertain and needs to be confirmed by future observations. The modelling approach developed here can be applied to other fish stocks for which catch-at-age data are available from several surveys.